Study of breakdown occurrence on the 11kV sewerage plant substation in UiTM Shah Alam: article - Abd Razak, Muhammad Syahmi (2014)
This paper describes the characteristics of environment of 11kV outdoor distribution substation that was affected to underground cable supply. There is some visual checking and site testing to detect breakdown on the cable and calculated cost involve comparing to suggested solution. Details inspection and testing are usually perform if any tripping or fault occur. In this case, breakdown of insulation cable was studied on how it could be solve with less cost spend. First, inspection and testing was performed in order to find point of fault. Then analysis of data and information was estimated that moisture is the main cause contributes to this case of fault. The affected part was identified so that repairing work could be done. It was confirmed that gear involved in switchgear truck, interconnected bus-bar and insulation of cable was affected and will not be able to operate. Repairing work cost was studied by comparing it with the suggested solution. The suggested solution is to eliminate Sewerage Plant substation from operation supported by availability considered.